Efisiensi Platforms Digital dalam Meningkatkan Kualitas Evaluasi Pembelajaran Pendidikan Agama Islam pada Kurikulum Merdeka - Muhammad Ridho Hakiki; Lubna; Mukhlis (Mataram University, 2026)
The transformation of information technology has shifted the evaluation paradigm from conventional written test-based models toward digital assessments that are more systematic, adaptive, and well-documented. This study employs a descriptive qualitative approach using a literature review method to examine the concept of Islamic Education (PAI) evaluation, the characteristics of the Merdeka Curriculum, and the utilization models of platforms such as Google Forms, Moodle, and Quizizz in the assessment process. The findings indicate that digital platforms contribute to improving objectivity, efficiency, transparency, and the speed of feedback through automatic grading features and learning outcome data analysis. In addition, digital platforms support the implementation of formative and authentic assessments in line with the principles of the Merdeka Curriculum. However, their implementation also faces several limitations, such as the potential for academic dishonesty, disparities in technology access, limitations in measuring affective and spiritual aspects, and reduced direct pedagogical interaction. Therefore, the effectiveness of digital platforms in PAI evaluation highly depends on teachers’ competencies in designing valid instruments and managing technology while maintaining orientation toward character building and Islamic values.